A hungry lion, or, a dwindling assortment of animals - Cummins, Lucy Ruth (Atheneum Books for Young Readers, 2016)
Members of a large group of animals, including a penguin, two rabbits, and a koala, disappear at an alarming rate but the hungry lion remains.